Behaviors of registered community nurses and midwives and their families in case of illness – a pilot study - Czabak-Garbacz, Róża; Kościk, Magdalena; Stasiuk, Weronika; Charytanowicz, Małgorzata; Borowicz, Barbara; Bednarczyk, Dorota (Polish Journal of Public Health, 2013)
Introduction. Community nurses and midwives who perform their work mainly in patients’ houses are subjected to many occupational hazards that frequently may lead to a disease, which next can be spread to their relatives, coworkers or patients. Therefore, the proper behavior of nursing staff in case of their own disease can be important for health of their environment. Aim. The present pilot study investigates the behavior of registered community nurses and midwives and their families in situation of illness. Material and methods. The investigation was performed with the use of anonymous questionnaires among the nursing staff in Bychawa region (Poland). Results. Behavior of community nurses and midviwes and their relatives in case of their illnes was similar – it included visiting a doctor and the use of pharmacotherapy, however sometimes without following all doctor’s orders and doing necessary check-ups. Frequent behavior was the use of OTC, first of all painkillers, vitamins and antipyretics but at times antibiotics as well. Discussion. Community nurses and midwives and their families sometimes do not behave properly in case of own disease – they sometimes do not follow the physician’s orders, for instance they do not undergo necessary check-ups and use drugs for self medication, among them antibiotics without necessary doctor’s prescription and supervision. This can make more difficult their correct diagnosis and treatment and may also have negative consequences on the public health, e.g. it can cause resistance to antibiotics Conclusions. The introduction of measures to improve the behavior of medical personnel in the event of illness, especially in the use of the doctor’s recommendations is an important task for the organizers of health care in Poland.